Ophthalmic Syndrome Differentiation System and Digital Chinese Medicine - Peng-Fei Jiang; Jun Peng; Ya-Sha Zhou; Yi-Chen Li; Qing-Hua Peng; Xiang-Dong Chen (KeAi Communications Co., Ltd., 2018)
ABSTRACT: In traditional Chinese medicine (TCM), ophthalmic syndrome differentiation is an ophthalmology-specific method for identifying syndromes based on the "Five Orbiculi" theory. It was devised by Professor Qing-Hua PENG through an unprecedented combination of syndrome element differentiation and ophthalmic clinical practices, based on the Clinical Terminology of Chinese Medical Diagnosis and Treatment-Syndromes of the National Standards of the People's Republic of China. This approach integrates an ophthalmic syndrome differentiation system with digital Chinese medicine (DCM), and proposes the extraction of syndrome elements of ophthalmic diseases from research on DCM. These elements are then quantified and organized to form a model of digital diagnosis and treatment specific to ophthalmology, which should help to achieve synergistic development of the ophthalmic syndrome differentiation system and DCM. Keywords: Ophthalmic syndrome differentiation, Digital Chinese medicine (DCM), Syndrome element differentiation, Dialectic of traditional Chinese Medicine, Five Orbiculi